The Effective Optimization Methods of Port Activity on the Basis of Algorithmic Model - A. Nyrkov; A. Shnurenko; S. Sokolov; S. Chernyi; V. Korotkov (International Journal of Electrical and Computer Engineering (IJECE), 2017)
The article considers the inland waterways (IW) within the international transport corridors as multiphase systems of mass service (SMS) and shows the distinction in calculation of the important indicator of system efficiency - the average total waiting time of vessel service in the serving subsystems, the application of genetic algorithms to increase the efficiency of reloading processes.